Transforming SME operations with real-time mobile POS and Firebase integration - Farel Naufal Azhari; Sutarman (International Journal of Science, Technology, Engineering and Mathematics)
Small and medium enterprises (SMEs) often struggle to efficiently manage sales transactions and inventory due to a lack of affordable, real-time technological solutions. Existing systems typically fail to offer seamless synchronization and proactive inventory management, which are crucial for resource-constrained businesses. This study addresses these challenges by developing a Mobile Point of Sale (mPOS) application integrated with Firebase, aimed at improving operational performance, reducing data inconsistencies, and supporting decision-making through real-time synchronization. The application was developed using a descriptive research approach, React Native for cross-platform compatibility, and Firebase for its real-time database features. Notable innovations include an automated low-stock notification system and an intuitive user interface for both staff and administrators, designed to streamline inventory management. Comprehensive testing and validation confirmed the system’s reliability, usability, and data consistency. However, the study was limited by its small-scale implementation and the absence of real-world retail trials. Future research should focus on its scalability, integration with advanced analytics, and application in larger retail settings.